2003
DOI: 10.1002/ps.650
|View full text |Cite
|
Sign up to set email alerts
|

Wind tunnel studies on spray deposition on leaves of tree species used for windbreaks and exposure of honey bees

Abstract: A wind tunnel study was conducted to determine pesticide deposition on commonly used windbreak tree species used as spray drift barriers and associated exposure of honey bees. Although it has been known that windbreaks are effective in reducing chemical drift from agricultural applications, there is still an enormous information and data gap on details of the dependence of the mechanism on the biological materials of the barriers and on standardization of relevant assessment methods. Beneficial arthropods like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Stands of vegetation over 1 m high have been shown to be efficient pollen collectors (Treu & Emberlin, 2000). In addition, experimental evidence of drift filtration of pesticides sprayed either under field conditions (Davis, Brown, Frost, Yates, & Plant, 1994;Miller, Lane, Walklate, & Richardson, 2000) or in a wind tunnel (Ucar, Hall, Tew, & Hacker, 2003) indicate that hedge barriers can reduce drift by up to 90%.…”
Section: Introductionmentioning
confidence: 96%
“…Stands of vegetation over 1 m high have been shown to be efficient pollen collectors (Treu & Emberlin, 2000). In addition, experimental evidence of drift filtration of pesticides sprayed either under field conditions (Davis, Brown, Frost, Yates, & Plant, 1994;Miller, Lane, Walklate, & Richardson, 2000) or in a wind tunnel (Ucar, Hall, Tew, & Hacker, 2003) indicate that hedge barriers can reduce drift by up to 90%.…”
Section: Introductionmentioning
confidence: 96%
“…However, the relation between deposition per curler and deposition per leaf area differed between hedgerows and between days, probably reflecting variation in factors such as leaf development and size, hedgerow porosity and weather conditions. 25,26) However, we have no indications of how collecting efficiency of the curlers depends on meteorological and technical factors.…”
Section: Discussionmentioning
confidence: 87%
“…The wind tunnel studies ensured bees were present in the direct spray from the application (76 mg on a target of 5625 cm 2; 13.5 µg/cm 2 ) and showed that at low wind speed deposits on flying bees were 4.6 ± 1.9 µg/bee and on dead bees 4.1 ± 0.9 µg/bee and at higher wind speeds 8.0 ± 2.1 µg/bee on flying bees and 7.9 ± 0.5 µg/bee on dead bees (Ucar et al, 2003). Given the application was only to the upper surface of the dead bees the surface area of a honeybee is 0.93 cm 2 (Johansen et al, 1983) this suggests that the maximum residue equated to 63% efficiency.…”
Section: Aggregate Exposure Of Foragers Following Spray Applicationsmentioning
confidence: 98%
“…The European food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. Flying bees 1.5 m/s 4.6 ± 1.9 μg/bee -46000 μg /kg 2.5 m/s 6.6 ± 2.2 μg./bee -66000 μg/kg 3.5 m/s 8.0 ± 2.1 μg/bee -80000 μg/kg Dead bees 1.5 m/s 4.1 ± 0.9 μg/bee -41000 μg/kg 2.5 m/s 6.7 ± 0.2 μg./bee -67000 μg/kg 3.5 m/s 7.9 ± 0.5 μg/bee -79000 μg/kg (Ucar et al, 2003) The present document has been produced and adopted by the bodies identified above as author. This task has been carried out exclusively by the author in the context of a contract between the European Food Safety Authority and the author awarded following a tender procedure.…”
Section: Supporting Publications 2012:en-340 17mentioning
confidence: 99%
See 1 more Smart Citation